Level of Reproductive Hormones in Men and Women after Successful Kidney Transplantation - Al-Lami, Makarim Q (Al-Nahrain Journal of Science, 2012)
This study was designed to shed a light on the reproductive function in men and women after successful kidney transplantation (KT). Forty five adult patients (25 men and 20 women) were included; these patients met the inclusion criteria (serum creatinine ≤ 1.4 mg/dl; glomerular filtration rate (GFR) ≥ 60 ml/min at least 3 months after KT). Twenty two healthy individuals (12 men and 10 women) were included as control group. Assessment of the renal function tests [blood urea, serum creatinine, and GFR] and determination of the level of the reproductive hormones [luteinizing hormone (LH), follicle-stimulating hormone (FSH), and prolactin (PRL) in men and women; and testosterone and 17-β-estradiol (E2) in the men and the women, respectively] had been carried out. The correlation between level of these hormones and the renal function tests was also studied in the patients. The results of the renal function tests showed that patients had higher blood urea and serum creatinine than the controls, while GFR was lower in the patients as compared to controls. Regarding to the reproductive hormones, it was found there were no significant differences in levels of LH, FSH and testosterone between men patients and men controls, while PRL was significantly (P